2017
DOI: 10.3390/w9040245
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years (1993–2007) of Surface Freshwater Storage Variability in the Ganges-Brahmaputra River Basin Using Multi-Satellite Observations

Abstract: Surface water storage is a key component of the terrestrial hydrological and biogeochemical cycles that also plays a major role in water resources management. In this study, surface water storage (SWS) variations are estimated at monthly time-scale over 15 years (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)) using a hypsographic approach based on the combination of topographic information from Advance Spaceborne Thermal Emission and Reflection Radiometer (ASTER) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…In particular, I SWS is 15 ± 0.9% in the Ganges-Brahmaputra. Our SWS/TWS amplitude ratio of 36% is close to the value (50%) reported in a previous study that combined observations from multiple satellites (Salameh et al, 2017). Geophysical Research Letters 10.1002/2017GL074684…”
Section: Surface Water's Impact On Terrestrial Water Storage Changementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, I SWS is 15 ± 0.9% in the Ganges-Brahmaputra. Our SWS/TWS amplitude ratio of 36% is close to the value (50%) reported in a previous study that combined observations from multiple satellites (Salameh et al, 2017). Geophysical Research Letters 10.1002/2017GL074684…”
Section: Surface Water's Impact On Terrestrial Water Storage Changementioning
confidence: 99%
“…Still, understanding of the relationship between TWS variations and changes in its individual components (groundwater, soil moisture, surface waters, snow, and vegetation water storage) has not advanced beyond small-scale studies based on in situ data (e.g., Rodell & Famiglietti, 2001). Although a few studies have demonstrated the impact that surface water storage (SWS) has on TWS in tropical basins (e.g., Papa et al, 2013;Pokhrel et al, 2013;Salameh et al, 2017), the vast majority of investigations on TWS decomposition systematically neglect SWS by assuming that its contribution to TWS is trivial (e.g., Rodell et al, 2007). Such studies have combined either model outputs or observations with GRACE data in order to estimate groundwater variations over the U.S. (Famiglietti et al, 2011), India (Chen et al, 2014;Girotto et al, 2017;Joodaki et al, 2014;Rodell et al, 2009;Tiwari et al, 2009), and the Middle East (Voss et al, 2013), among other regions.…”
Section: Introductionmentioning
confidence: 99%
“…In three different regions of the High Plains Aquifer, r 2 between in situ and GRACE-based estimates increased from 0.18 to 0.73 and 0.79 in the Northern High Plains Aquifer, 0 to 0.81 and 0.93 in the Central High Plains Aquifer and from 0.02 to 0.44 and 0.72 in the Southern High Plains Aquifer, USA, between 2003 and 2013, taking into account SMS, SMS+IRR, or SMD (both methods give the same results) and IRR [111]. In large river basins with extensive floodplains, SWS cannot be neglected, representing, for instance, between 40% and 50% of the annual variations of TWS as in the Amazon [133,134], Orinoco [135], and Ganges [136,137] basins. Regional SWS water changes can be estimated using multi-satellite observations, such as the synergy between inundation extent from satellite images and either satellite altimetry or Global Digital Elevation Models (GDEM).…”
Section: Impacts Of the Non Inclusion Of Hydrological Water Compartmementioning
confidence: 99%
“…The Himalayas from Nepal provides fresh water to India and Bangladesh, the Amazon forest extends across various countries in South America and supports them, and cargo vessels in the sea cross different international borders. (117)(118)(119) Thus, stakeholders should adopt collaborative measures for the conservation of natural resources and the prevention of natural disasters.…”
Section: Application Of Rs and Geospatial Technologies For Sdgsmentioning
confidence: 99%